RDL mutations in Guangxi Anopheles sinensis populations along the China–Vietnam border: distribution frequency and evolutionary origin of A296S resistance allele - Liu, Nian (Malar J, 2020)
BACKGROUND: Malaria is a deadly vector-borne disease in tropical and subtropical regions. Although indigenous malaria has been eliminated in Guangxi of China, 473 confirmed cases were reported in the Northern region of neighbouring Vietnam in 2014. Considering that frequent population movement occurs across the China–Vietnam border and insecticide resistance is a major obstacle in disease vector control, there is a need to know the genotype and frequency of insecticide resistance alleles in Anopheles sinensis populations along the China–Vietnam border and to take action to prevent the possible migration of insecticide resistance alleles across the border. METHODS: Two hundred and eight adults of An. sinensis collected from seven locations in Guangxi along the China–Vietnam border were used in the investigation of individual genotypes of the AsRDL gene, which encodes the RDL gamma-aminobutyric acid (GABA) receptor subunit in An. sinensis. PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) analysis was deployed to genotype codon 345, while direct sequencing of PCR products was conducted to clarify the genotypes for codons 296 and 327 of the AsRDL gene. The genealogical relation of AsRDL haplotypes was analyzed using Network 5.0. RESULTS: Three putative insecticide resistance related mutations (A296S, V327I and T345S) were detected in all the seven populations of An. sinensis in Guangxi along the China–Vietnam border. The resistance-conferring A296S mutation was found to be widely distributed and present at notably high frequencies (78.8% to 100%). Relatively lower frequencies of mutations V327I (26.9% to 53.2%) and T345S (0% to 28.8%) were observed. The V327I or T345S always occurred in the presence of A296S. Evolutionary analysis of 21 AsRDL haplotypes indicated multiple origins of the A296S and V327I mutations. CONCLUSION: The resistance A296S allele was present at high frequencies in the An. sinensis populations along the China–Vietnam border, indicating a risk of resistance to insecticides targeting RDL. The double mutations (A296S + V327I) may have evolved from alleles carrying the A296S mutation by scaffolding the additional mutation V327I, and A296S allele may have multiple evolutionary origins. These findings will help inform strategies for vector control and malaria prevention.